ICEA of Mycoplasma agalactiae: a new family of self‐transmissible integrative elements that confers conjugative properties to the recipient strain. Issue 6 (16th August 2013) - Dordet Frisoni, Emilie; Marenda, Marc Serge; Sagné, Eveline; Nouvel, Laurent Xavier; Guérillot, Romain; Glaser, Philippe; Blanchard, Alain; Tardy, Florence; Sirand‐Pugnet, Pascal; Baranowski, Eric; Citti, Christine
Summary Horizontal gene transfer (HGT) is a major force of microbial evolution but was long thought to be marginal in mycoplasmas. In silico detection of exchanged regions and of loci encoding putative Integrative Conjugative Elements (ICE) in several mycoplasma genomes challenged this view, raising the prospect of these simple bacteria being able to conjugate. Using the model pathogen Mycoplasma agalactiae, we demonstrated for the first time that one of these elements, ICEA, is indeed self‐transmissible. As a hallmark of conjugative processes, ICEA transfers were DNase resistant and required viable cells. ICEA acquisition conferred ICE‐negative strains with the new ability to conjugate, allowing the spread of ICEA. Analysis of transfer‐deficient mutants indicated that this process requires an ICEA‐encoded lipoprotein of unknown function, CDS14. Formation of a circular extrachromosomal intermediate and the subsequent chromosomal integration of ICEA involved CDS22, an ICEA‐encoded product distantly related to the ISLre2 transposase family. Remarkably, ICEA has no specific or no preferential integration site, often resulting in gene disruptions. Occurrence of functional mycoplasma ICE offers these bacteria with a means for HGT, a phenomenon with far‐reaching implications given their minute‐size genome and the number of species that are pathogenic for a broad host‐range.